Evaluación del efecto de un surfactante comercial en emulsiones directas, creadas a partir de aceite de palma amazónica "Canangucha", desde un punto de vista termodinámico (2017)
In the chemical industry, surfactants are commonly used in the generation of emulsions. These types of mixtures are a vital source for the construction of products, where their components are based on the specific chemical structures and formulations of each partner compound, eg cosmetics. In addition, it has been found that the oil of Amazonian palms (milPesos, milpesillos, asaí, canangucha, among others) can be used in the formulation of these emulsions, and from criteria of stability in their physical and chemical characteristics, determine if they are a Viable compound for use by the industry. In this project, we intend to evaluate the effect of two commercial surfactants (Tween 80ª and Span 20ª) from a thermodynamic point of view, in a direct emulsion formulated with canangucha oil. The choice of surfactant concentration for each test was based on the required HLB of the oil. To analyze this effect, two properties were analyzed: the interfacial tension and the required heat flux associated with the change of the phase transition temperatures in the emulsion. The first one allows to analyze the behavior of the two phases of the emulsion (continuous and dispersed) when the attraction and repulsion forces interact between these phases, and in terms of the calorimetry, it was measured by means of the differential scanning method. In the same way, from the results the determination of an association with the stability of the emulsions according to results of droplet size, particle distribution etc, were obtained that were obtained simultaneously to the realization of the project.--Tomado del Formato de Documento de Grado.